The World Bank Research Program 2004 : Abstracts of Current Studies - World Bank (The World Bank, 2005)
The World Bank's research is intended to address critical issues and problems facing member governments in developing and transition economies. How can the governments of the poorest countries generate enough revenue to provide the education and health services essential to reducing poverty and promoting growth and development? How can poor countries attract investors to build the infrastructure their economies need? How can they develop systems to bring clean water to the 2 billion people without it today? How can they train teachers and bring to class the 115 million children who have not yet received any education? And how can rich countries be persuaded to lower market barriers, helping to reverse the decline in export prices for poor countries that has left them earning less from trade today than in the 1970s? These are the types of questions that are addressed in this edition of The World Bank Research Program: Abstracts from Current Studies. This volume reports on research projects initiated, under way, or completed from July 2003 through June 2004. It covers 151 research projects on several broad development related issues, including agriculture, health, education, environment, infrastructure, investment climate, and more. The abstract for each project describes the questions addressed, the analytic methods used, the findings to date, and policy implications